Critical Issues in the Development of Hungarian Public Health with Special Regard to Spatial Differences - Orosz, Éva (Discussion Papers, 1986)
The present study examines some important problems facing the Hungarian health system, particularly with regard to identifying spatial differences in the provision of health care. The study consists of two parts: the first presents a summary of the relevant literature; while the second discusses the research findings. The remainder of the introduction provides an overview of the post-WWII Hungarian health system to help better acquaint readers who may not be familiar with the situation here. Besides outlining the tensions and contradictions whose solution is in progress in Hungarian public health, the study’s basic aim is to describe the main tendencies in regional differences of public health infrastructure and of the underlying factors.